2021
DOI: 10.7150/ijbs.62471
|View full text |Cite
|
Sign up to set email alerts
|

Rutin attenuates Sorafenib-induced Chemoresistance and Autophagy in Hepatocellular Carcinoma by regulating BANCR/miRNA-590-5P/OLR1 Axis

Abstract: Rutin, the main component of Potentilla discolor Bunge, was proven to exhibit anti-tumor properties. Sorafenib (SO) is conventionally used in chemotherapy against hepatocellular carcinoma (HCC), but acquired resistance developed during long-term therapy limits its benefits. This study aimed to explore the molecular mechanism of rutin in SO-induced autophagy and chemoresistance in HCC. Sixty-eight paired HCC patients who received the same chemotherapy treatment were obtained. We also established two SO resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 48 publications
0
29
0
1
Order By: Relevance
“…According to the results of the present experiments, the subcutaneous xenogeneic model was relatively stable ( Figure S1 ). Therefore, an implanted subcutaneous GBM was established by injecting U251 and A172 cells into Balb/c nude mice, which were then treated with 1 (low dose) or 5 (high dose) mg/kg PSPD3R every 2 days 24 to validate whether the in vitro anti-tumor effect of PSPD3R is also evident in vivo ( Figure 2 A). The xenografts in the PSPD3R-treated mice grew more slowly than those in the placebo-treated control mice.…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of the present experiments, the subcutaneous xenogeneic model was relatively stable ( Figure S1 ). Therefore, an implanted subcutaneous GBM was established by injecting U251 and A172 cells into Balb/c nude mice, which were then treated with 1 (low dose) or 5 (high dose) mg/kg PSPD3R every 2 days 24 to validate whether the in vitro anti-tumor effect of PSPD3R is also evident in vivo ( Figure 2 A). The xenografts in the PSPD3R-treated mice grew more slowly than those in the placebo-treated control mice.…”
Section: Resultsmentioning
confidence: 99%
“…At a dose of 20 μM, these researchers found that this flavonoid acts as a chemo-sensitizing agent by improving the anti-tumor effect of two chemotherapeutic agents (methotrexate and cyclophosphamide). Furthermore, rutin improved the in vivo efficacy of another anti-cancer drug (sorafenib) in a xenograft model of human HCC [ 42 ]. As seen with quercetin and berberine, another natural flavone called hispidulin enhanced cellular chemo-sensitivity by inhibiting the expression of the transcription factor HIF-1α via AMPK signaling in gallbladder cancer [ 43 ].…”
Section: Dietary Phenolic Compounds Improving the Chemosensitivity Of...mentioning
confidence: 99%
“…The downregulation of lncRNA MALAT1 by propofol results in inhibiting autophagy and promoting gastric cancer cells sensitive to cisplatin ( 210 ). A recent study demonstrated that rutin, the main component of Potentilla discolor Bunge, reverses sorafenib resistance by inhibiting autophagy through the BANCR/miRNA-590-5P/OLR1 axis in HCC ( 211 ). Furthermore, it is urgent to look for efficient miRNA delivery system for miRNA mimics that can’t enter cells efficiently on its own.…”
Section: Targeting Mirna/autophagy Axis To Combat Chemoresistancementioning
confidence: 99%